An Empirical Investigation on Annual Reporting Practices of Malaysian State Islamic Religious Councils: Issues and Challenges - Rosnia Masruki; Noor Azlinna Azizan (USIM Press, 2024)
Vol. 31 (2020): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [August 2020]